STRATEGI PENGEMBANGAN KAWASAN PETERNAKAN KERBAU RAWA DI KABUPATEN HULU SUNGAI SELATAN - Alpianor Alpianor; Danang Biyatmoko; Hafizianor Hafizianor; Muhammad Husaini (EnviroScienteae, 2017)
This study aims to: 1) analyze the management of swamp buffalo husbandry in Hulu Sungai Selatan, and 2) formulate the strategies for developing swamp-buffalo husbandry in Kabupaten Hulu Sungai Selatan Regency. The research was conducted in four villages, namely: Desa Bajayau Tengah in Kecamatan of Western Daha, Desa Pandak Daun, Desa Hakurung and Desa Hamayung in Kecamatan Daha Utara, Kabupaten Hulu Sungai Selatan, South Kalimantan province from April to July 2016. To investigate the management of swamp-buffalo husbandry in Kabupaten Hulu Sungai Selatan, a descriptive analysis is used by interviewing the farmers and the government concerning the capacity of farmers, the capacity of facilities, and the capacity of management. To find out the strategies needed in developing swamp-buffalo husbandry in Kabupaten Hulu Sungai Selatan, the combination of strengths, weaknesses, opportunities, threats (SWOT) analysis with analytical hierarchy process (AHP) was applied. The management of swamp buffalo husbandry in Kabupaten Hulu Sungai Selatan in relation to the existing management capacity has not been implemented properly. The management capacity could be developed through non-formal education, such as training and counseling to farmers through the group of farmers because they were supported by a) the capacity of farmers. such as age, experience and business scale which were quite good as well as the improvement of education and the farmer responsibilities; and b) the capacity of facilities such as the buffalo grass feed, marketing, pretty good institutions as well as the improved buffalo seeds and the swamp- buffalo stall/latch. The strategies for swamp-buffalo husbandry in Kabupaten Hulu Sungai Selatan recommended the strategy of strengths - opportunities (SO). The strategies that can be done are to increase the population of swamp buffaloes supported by technologies for breeding, feeding, management and marketing and agro-tourism development by empowering the farmer groups. The strategies which support the development of swamp buffalo husbandry in Kabupaten Hulu Sungai Selatan are: a) the assistance acceleration of the technology adoption to increase the productivity of swamp buffaloes as well as to improve the infrastructure and facilities for swamp-buffalo husbandry businesses; b) the increase of business efficiency of swamp- buffalo husbandry and to increase the cooperation with other institutions; c) the improvement of the business systems of swamp buffalo husbandry and the strengthening of the groups of farmers  of swamp buffalo husbandry in order that the farmer groups  have bargaining power.